Чтобы решить уравнение с логарифмами, нужно их привести к одинаковому основанию:
По свойству логарифмов:
3 = log2 (2^3) = log2 (8)
Решаем уравнение:
х-7=8
х=15
Проверка:
log2 (15-7) = log2 (8) = log2 (2^3) = 3log2 (2) = 3
15.
Пошаговое объяснение:
ОДЗ: х - 7 > 0
х > 7
log2 (x-7)=3
х - 7 = 2^3
х - 7 = 8
х = 15
log2 (15-7)=3
log2 (8) = 3 - верно.
Чтобы решить уравнение с логарифмами, нужно их привести к одинаковому основанию:
По свойству логарифмов:
3 = log2 (2^3) = log2 (8)
Решаем уравнение:
х-7=8
х=15
Проверка:
log2 (15-7) = log2 (8) = log2 (2^3) = 3log2 (2) = 3
15.
Пошаговое объяснение:
ОДЗ: х - 7 > 0
х > 7
log2 (x-7)=3
х - 7 = 2^3
х - 7 = 8
х = 15
Проверка:
log2 (15-7)=3
log2 (8) = 3 - верно.